Salvage therapy for recurrent glioblastoma multiforme: a multimodal approach combining fluorescence-guided resurgery, interstitial irradiation, and chemotherapy. (December 2014) - Archavlis, Eleftherios; Tselis, Nikolaos; Birn, Gerhard; Ulrich, Peter; Zamboglou, Nikolaos
<x content-type="archive" xml:space="preserve">Abstract</x> Objectives: Several studies have revealed that different salvage treatments in glioblastoma multiforme patients presenting a recurrence have limited palliative treatment options. The aim of this study was to evaluate the utility and limitations of multimodal salvage treatments in recurrent glioblastoma multiforme patients combining 5-aminolevulinic acid (5-ALA) fluorescence-guided resurgery, interstitial irradiation, and dense dose temozolomide chemotherapy (ddTMZ). Methods: Seventeen consecutive patients with recurrent globlastoma multiforme underwent a combined scheme of salvage treatments including fluorescence-guided reoperation, high dose rate (HDR) brachytherapy, and ddTMZ chemotherapy and were included in this prospective study. This multimodal treatment group was compared with a 1∶1 matched historical control group of 17 patients who have been treated with intensive temozolomide chemotherapy as the only treatment modality. All patients were previously treated with surgery of the primary pathology, concomitant, and adjuvant radiochemotherapy with temozolomide. Results: Median follow-up was 32 months (range: 28–36 months). Median survival was 9 months for the entire cohort after salvage treatment and can be translated into a 3-month improvement in survival compared to the control group of patients with glioblastoma recurrence treated with temozolomide alone (P = 0·043). Complications rates of multimodal salvage treatment were comparable with the temozolomide control group. Discussion: Our experience suggests that a combined salvage treatment plan have the advantages of all three methods and, thus, provide additional survival benefit and can be considered in selected patients affected by recurrent high grade gliomas. Nonetheless, more cases and additional studies are necessary to further prove the advantages of this multimodal treatment.